In-Vitro Evaluation of Sun Protection Factors of Sunscreens Marketed in Sirte by Ultraviolet Spectrophotometry - Himeedah Zayd, Ibrahim Ahmed Alsaeh, Fathia A. Mosa , Gazala Mohamed Ben-Hander (Journal of Pure & Applied Sciences, 2019)
The Sunscreen products that contain different active ingredients which can affect the sunlight by absorbing, reflect or scatter it depends on the nature of these products. The effectiveness of a sunscreen product can be evaluated by determining the sun protection factor (SPF). This research aimed to determine the sun protection factor (SPF) values of six sunscreens commercial product by UV-Visible Spectroscopy. In this study, the absorption values of some cosmetic products as sunscreens (creams, lotions and foundations) were measured using the ultraviolet spectrophotometer. The Mansur equation was applied to calculate SPF values for each cosmetic product. The sun protections labelled values of these commercially available sunscreens were in the range (10-90). Therefore, this spectrophotometric method is fast, straightforward and can be used to determine the SPF values in cosmetic.